Transient increases in intracellular calcium and reactive oxygen species levels in TCam-2 cells exposed to microgravity - Morabito, C. (Sci Rep, 2017)
The effects of microgravity on functions of the human body are well described, including alterations in the male and female reproductive systems. In the present study, TCam-2 cells, which are considered a good model of mitotically active male germ cells, were used to investigate intracellular signalling and cell metabolism during exposure to simulated microgravity, a condition that affects cell shape and cytoskeletal architecture. After a 24 hour exposure to simulated microgravity, TCam-2 cells showed 1) a decreased proliferation rate and a delay in cell cycle progression, 2) increased anaerobic metabolism accompanied by increased levels of intracellular Ca(2+), reactive oxygen species and superoxide anion and modifications in mitochondrial morphology. Interestingly, all these events were transient and were no longer evident after 48 hours of exposure. The presence of antioxidants prevented not only the effects described above but also the modifications in cytoskeletal architecture and the activation of the autophagy process induced by simulated microgravity. In conclusion, in the TCam-2 cell model, simulated microgravity activated the oxidative machinery, triggering transient macroscopic cell events, such as a reduction in the proliferation rate, changes in cytoskeleton-driven shape and autophagy activation.